FROM UNIVERSITY PORTAL TO KNOWLEDGE MANAGEMENT SYSTEM - Ngô, Văn Tháp (Tạp chí khoa học, 2023)
Quality has always been an essentiality of a university. With the development of IT, especially web technology, Web Portal has become a management tool, aiding university in utilising resources, gaining a competitive advantage in university education This paper presents Web Portal as a knowledge management system, a technological solution for university in targeting true education.